2015
DOI: 10.1590/s1517-838246220140234
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori in children in eastern Turkey and molecular typing of isolates

Abstract: The objectives of the present study were to determine Helicobacter pylori via culture, polymerase chain reaction and histopathological diagnosis in 101 children ranging in age from 4 to 18 years, to identify the association among restriction fragment length polymorphism types and clinical disease and to investigate the relationships among different isolates of H. pylori in different age groups. We observed a high prevalence of H. pylori infections in children between the ages of 13 and 18 (75.8%), while childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
1
23
3
Order By: Relevance
“…Prevalence of H. pylori infection was evaluated by Ozbey et al . in eastern Turkey in 101 symptomatic children and adolescents undergoing endoscopy.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…Prevalence of H. pylori infection was evaluated by Ozbey et al . in eastern Turkey in 101 symptomatic children and adolescents undergoing endoscopy.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…The prevalence of H. pylori was found 49.5% in 327 healthy Turkish school children (3‐12 years old), and it was shown that prevalence of the infection increased with age, and reached 63% at 11 years of age and older using 13 Carbon‐urea breath test ( 13 C‐UBT) . In eastern Turkey, H. pylori prevalence was found in 63.2% in 8‐ to 14‐year‐old children by histological examination . Helicobacter pylori incidence was found in 51.8% in children with FD in Brazil .…”
Section: Introductionmentioning
confidence: 99%
“…Turkey is considered to be an interesting region as it may receive influences from Asian and Western countries showing high and low H. pylori prevalence rates, respectively . In Eastern Turkey, H. pylori has been detected in 23.6% up to 75.8% of the children . For the first time, a prevalence rate of 30.9% was demonstrated in children from Southern Turkey.…”
Section: Discussionmentioning
confidence: 99%